Advancing Artificial Intelligence Literacy in Teacher Education Through Professional Partnership Inquiry - Michelle Kelley; Taylar Wenzel (Education Sciences, 2025)
Artificial Intelligence (AI) has increasingly been integrated into daily life, yet many individuals, including teacher candidates, remain unaware of its presence, despite the rise in Generative AI and its influence on personal and professional spaces. AI offers promising advancements in education by enhancing efficiency, streamlining administrative tasks, and personalizing learning experiences. Recognizing the need to address AI’s role within their instructional practice and teacher preparation program, the authors describe their AI journey, detailing a multi-phase approach to integrating AI into higher education through individual exploration, faculty partnerships, pilot study implementation, and expanded partnerships and professional development. This article includes concrete examples of how a semester-long action research project was intentionally reimagined to align with AI-driven learning. Using the Digital Education Council’s AI Literacy Framework as a guiding structure, the authors examine the competencies necessary for AI literacy and leadership in education. This retrospective review highlights lessons learned, challenges faced, and emerging strategies for fostering responsible AI integration in K-12 and teacher preparation programs.